1999
DOI: 10.1074/jbc.274.26.18552
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 and Caspase Inhibition Cooperate to Inhibit Tumor Necrosis Factor-α-induced Cell Death in a Bcl-2 Cleavage-independent Fashion

Abstract: The ability of proteins of the Bcl-2 family to either induce or inhibit apoptosis is dependent on both cell type and the apoptotic stimulus. We have shown in the murine pro-B cell line FL5.12 that Bcl-2 is incapable of inhibiting tumor necrosis factor ␣ (TNF␣)-induced cell death and is cleaved during this process. One potential explanation for this observation is that caspase activation directly or indirectly inhibits Bcl-2 function. It has been suggested that caspase cleavage of Bcl-2 is responsible for its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 36 publications
(39 reference statements)
2
33
0
1
Order By: Relevance
“…Cells were harvested, lysed and subjected to western blotting as described previously (Johnson and Boise, 1999). Primary antibody against caspase-3 (Cell Signaling Technology) was used.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were harvested, lysed and subjected to western blotting as described previously (Johnson and Boise, 1999). Primary antibody against caspase-3 (Cell Signaling Technology) was used.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Primary antibody against caspase-3 (Cell Signaling Technology) was used. Actin (Sigma) was used as a loading control and was visualized as described previously (Johnson and Boise, 1999).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Studies have demonstrated that cleavage of Bcl2 and Bcl-X L by caspases, the molecular scissors effecting intracellular apoptosis, may affect their antiapoptotic function. [90][91][92] Caspases are cysteine proteases that cleave target proteins specifically at aspartic acid residues. 93 Caspases have emerged as critical players in apoptotic pathways.…”
Section: How Might Bcl2 Phosphorylation Regulate Functionmentioning
confidence: 99%
“…92 The deletion of the BH4 domain and resulting possible 'exposure' of the BH3, pore/channel forming region apparently can turn Bcl2 from an anti-apoptotic to pro-apoptotic molecule, much like a Jekyll and Hyde plot. 91 The putative caspase cleavage site for Bcl-X L occurs within the flexible loop region (at D61). 91 Other mechanisms involving the proteolytic degradation of Bcl2 may also be involved in its regulation.…”
Section: How Might Bcl2 Phosphorylation Regulate Functionmentioning
confidence: 99%
See 1 more Smart Citation